(untitled) (Scientific journal of the Fergana State University, 2023)
This article, basing on the use of various sources: archival, periodicals, historical literature, reveals a poorly researched fact in native history, like applying of experience and knowledge of the former imperial elite of Turkestan in managing the region after the February Revolution of 1917. In addition, the perception of the former imperial officials of bourgeois revolution, their thoughts about the future of Turkestan and their own place in the region have been represented.